Maintaining vocational education: strategies of a public institution aimed at adolescents in social vulnerability - Lilian Dias Ennes; Camila Pureza Guimarães da Silva; Tânia Cristina Franco Santos; Patrícia dos Santos Augusto; Gabriella Picoli dos Santos Faustino; Antonio José de Almeida Filho (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to analyze the political and administrative strategies for maintaining the courses at the Healthcare Professional Unit and the Hospital da Criança e do Adolescente Study Center of the Brazilian Center for Childhood and Adolescence Foundation. Methods: a historical study, with sources consisting of journalistic articles and official documents, in addition to eight participants. Data were collected from May to December 2021 and analyzed based on articles on vocational education and educational policies at national and state levels. The time frame covers the years 1990 to 1997. Results: strategies adopted by workers culminated in changes at the Centro Piloto Quintino, with the structuring of the Comprehensive Learning Center, and the maintenance of courses at the Healthcare Professional Unit. Final Considerations: the strategies resulted in the restructuring and redefinition of the space that was previously intended to stigmatize adolescents in situations of social vulnerability.